2022
DOI: 10.1111/bjep.12560
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and emotional, behavioural and cognitive aspects of self‐regulated learning: Direct and indirect relations with academic achievement and life satisfaction

Abstract: Background Adaptability regulates individuals' cognitive, behavioural and emotional responses to new, unexpected and uncertain situations, but to date no study has analysed whether adaptability contemporarily favours cognitive, behavioural and emotional aspects of learning. Aims This study aims to address this gap by examining (i) the direct relations between adaptability and achievement emotions, self‐regulated learning strategies and academic self‐efficacy and (ii) the direct and indirect relations between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 87 publications
1
13
0
Order By: Relevance
“…Our results, in line with recent evidence ( Feraco et al 2023b ; Muenks et al 2017 ), showed that soft skills are distal from academic achievement, but highlighted their role as possible predictors of study-related factors that mediate the association between soft skills and academic achievement ( Weber and Harzer 2022 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results, in line with recent evidence ( Feraco et al 2023b ; Muenks et al 2017 ), showed that soft skills are distal from academic achievement, but highlighted their role as possible predictors of study-related factors that mediate the association between soft skills and academic achievement ( Weber and Harzer 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…It might probably be that it is this common variance that explains its association with the behavioral and motivational aspects of study-related aspects, as suggested by studies on the general factor of soft skills (e.g., Feraco et al 2022a ). Interestingly, the main role that adaptability assumed in the network is linked with achievement emotions, an effect that only recently, and mainly because of the stressful COVID-19 pandemic, captured the attention of scholars ( Feraco et al 2023b ; Zhang et al 2021 ). Future studies should then better understand the mechanism underlying the association between adaptability and emotions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Adaptability Scale (Martin et al, 2012; Italian adaptation by Feraco, Casali, Ganzit & Meneghetti, 2023) measures the ability to efficiently regulate psycho‐behavioral functions in response to new and uncertain conditions. It includes nine items on a 7‐point Likert scale (e.g., “I am able to adjust my thinking or expectations to assist me in a new situation”).…”
Section: Methodsmentioning
confidence: 99%